2015
DOI: 10.17015/ejbe.2015.016.06
|View full text |Cite
|
Sign up to set email alerts
|

Oil Price Shocks and Macroeconomic Activities in Asean-5 Countries: A Panel VAR Approach

Abstract: The paper investigates the asymmetric effects of oil price shocks on real economic activities in ASEAN-5 from 1991 to 2014 using an unrestricted panel Vector Auto Regressive (VAR) method. Results from the impulse response function (IRFs) show evidence of an asymmetric relationship between oil prices and economic activities. Specifically, positive oil price shock measures negatively affect output growth both in the short term and in the long term. For oil price decrease specifications, real output responds nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 25 publications
1
25
2
1
Order By: Relevance
“…Similarly, Donayre and Wilmot [22] and Farzanegan and Markwardt [30] also found an asymmetric effect in their studies. As for the case of ASEAN countries, Aziz and Dahalan [25] used a panel VAR model for the ASEAN-5 countries consisting of Indonesia, Malaysia, Philippines, Singapore and Thailand. Overall the studies suggest asymmetric effect for the case of ASEAN-5.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Donayre and Wilmot [22] and Farzanegan and Markwardt [30] also found an asymmetric effect in their studies. As for the case of ASEAN countries, Aziz and Dahalan [25] used a panel VAR model for the ASEAN-5 countries consisting of Indonesia, Malaysia, Philippines, Singapore and Thailand. Overall the studies suggest asymmetric effect for the case of ASEAN-5.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With regards to the endogenous growth theory, there are several numbers of variables that are significantly correlated with growth regression models, including but not limited to initial level of income, investment rate, various measures of education and certain policy indicators [37,38]. Furthermore, based on the work of Aziz and Dahalan [25], Donayre and Wilmot [22], and Nusair [10], it is apparent that oil price also plays an important role in the determination of the economic growth of net oil-exporting countries. In line with that, the following multivariate specification is employed, as inspired by the growth regression model, which is broadly similar to Levine and Renelt [39], Campos [40], and Azman-Saini et al [41], with the addition of oil price as an explanatory variable:…”
Section: Empirical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cholesky decomposition strategy entails a contemporaneous relationship among the variables. The first variable in the VAR system influences the other variables contemporaneously, while the following variables in the VAR impact the variables listed earlier only in their lag form [Aziz, Dahalan, 2015]. Considering that the variables correspond to the Cholesky decomposition, the order (ren; gdp; ep) is then imposed from the most to the least exogenous.…”
Section: Methodsmentioning
confidence: 99%
“…He found that the growth hypothesis is supported for India, Malaysia, Mexico, and South Africa, while the neutrality hypothesis has been found in China, Indonesia, the Philippines, Thailand, and Turkey, and the growth detriment hypothesis has been diagnosed for Brazil. Aziz and Dahalan (2015) assessed impacts of oil price shocks on real economic activities in ASEAN-5 for the period 1991-2014. Results indicated that positive oil price shock measures negatively influence output growth both in the short term and long term.…”
Section: Empirical Reviewmentioning
confidence: 99%